2008
DOI: 10.1002/uog.6272
|View full text |Cite
|
Sign up to set email alerts
|

Modified myocardial performance index for evaluation of fetal cardiac function in pre‐eclampsia

Abstract: Objective To assess cardiac function by means of the modified myocardial performance index (Mod-MPI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
5
50
0
1
Order By: Relevance
“…Throughout gestation, there was a small increase in the Mod-MPI, a comparable result with the one and only previously published reference range [14]. We include a summary of the previously published literature in table 2 [6,12,14,15,16]. However, our study demonstrates marked differences in the actual values of the calculated Mod-MPI and on the effect of fetal heart rate on the Mod-MPI.…”
Section: Discussionmentioning
confidence: 34%
See 1 more Smart Citation
“…Throughout gestation, there was a small increase in the Mod-MPI, a comparable result with the one and only previously published reference range [14]. We include a summary of the previously published literature in table 2 [6,12,14,15,16]. However, our study demonstrates marked differences in the actual values of the calculated Mod-MPI and on the effect of fetal heart rate on the Mod-MPI.…”
Section: Discussionmentioning
confidence: 34%
“…Friedman et al [4] first used the same cardiac cycle by defining a different position of the Doppler sample volume, and then Hernandez-Andrade et al [5] in 2005 proposed a modified MPI (Mod-MPI) based on the use of mitral (MV) and aortic valve (AoV) clicks as landmarks for the measurement of time intervals. There has been subsequent growth in research into fetal MPI for application in normal and complicated pregnancies [6,7,8,9,10,11]. Although individual units have demonstrated reproducibility in fetuses [5,12], published normal ranges have been widely variable, causing concern as to the validity of this new technique.…”
Section: Introductionmentioning
confidence: 99%
“…Also, no stratified analysis for cases with and without pre-eclampsia was performed. However, recent studies have demonstrated that pre-eclampsia does not have any influence on these cardiovascular Doppler parameters 36,37 . Finally, as DV abnormalities were a criterion for delivery, no conclusions can be drawn regarding a temporal relationship of DV changes with other signs of advanced fetal deterioration.…”
Section: Discussionmentioning
confidence: 96%
“…While Chen et al [103] found a significant difference in the right and left MPIs between the control group and pregnancy-induced hypertension syndrome group, there is no consistent data currently available on pregnancies complicated with pre-eclampsia [29]. …”
Section: Clinical Application Of Mpimentioning
confidence: 99%
“…An increased IRT is generally accompanied by a reduced ET, with the ICT the most stable MPI parameter [4]. The MPI has been used to demonstrate fetal cardiac dysfunction in a number of pathologies including maternal diabetes [11,12,13,14,15,16], TTTS [7,17,18,19,20,21,22], congenital heart malformations [23,24,25,26,27,28], pre-eclampsia [29], IUGR [11,30,31,32,33,34], and other fetal conditions [35,36,37,38]. Several studies have proposed methods to improve the repeatability of fetal MPI by defining fixed machine settings [39] and using the clicks of the aortic and mitral valves as landmarks to delineate the constituent time intervals [9,40,41].…”
Section: Introductionmentioning
confidence: 99%